Protein-Energy Malnutrition Alters Thermoregulatory Homeostasis and the Response to Brain Ischemia - E. Smith, Shari; J. Prosser-Loose, Erin; Colbourne, Frederick; G. Paterson, Phyllis (Current Neurovascular Research, 2011)
Co-existing protein-energy malnutrition (PEM), characterized by deficits in both protein and energy status, impairs functional outcome following global ischemia and has been associated with increased reactive gliosis. Since temperature is a key determinant of brain damage following an ischemic insult, the objective was to investigate whether alterations in post-ischemic temperature regulation contribute to PEM-induced reactive gliosis following ischemia. Male Sprague-Dawley rats (190-280g) were assigned to either control diet (18% protein) or PEM induced by feeding a low protein diet (2% protein) for 7 days prior to either global ischemia or sham surgery. There was a rapid disruption in thermoregulatory function in rats fed the low protein diet as assessed by continuous recording of core temperature with bio-electrical sensor transmitters. Both daily temperature fluctuation and mean temperature increased within the first 24 hours, and these remained significantly elevated throughout the 7 day pre-ischemic period (p < 0.027). In the immediate post-surgical period, PEM decreased body temperature to a greater extent than that in well-nourished controls (p = 0.003). The increase in daily temperature fluctuation caused by PEM persisted throughout the 7 day post-surgical period (p < 0.001), and this interacted with the effects of global ischemia on days 8 (p = 0.018) and 11 (p = 0.021). The astrocytic and microglial responses induced at 7 days after global ischemia were not influenced by PEM, but this preliminary analysis needs to be confirmed with a more reliable global ischemia model. In conclusion, exposure to a low protein diet rapidly impairs the ability to maintain thermoregulatory homeostasis, and the resultant PEM also diminishes the ability to thermoregulate in response to a challenge. Since temperature regulation is a key determinant of brain injury following ischemia, these findings suggest that the pathophysiology of brain injury could be altered in stroke victims with coexisting PEM.
Keywords: Homeostasis